HARMONICS IMPACT ON LOW VOLTAGE (LV) GRID CONNECTED SOLAR PHOTOVOLTAIC (GCSPV) SYSTEM - Abdelhafiz Musa, Ahmed Abdelrahman (IRC, 2016)
There is a growing concern about environmental issues and the protection of environment. The demand of solar power generation through installation of grid connected photovoltaic solar panels for small-scale electricity generation is expected to grow in most part of the world due to essential advantages from the system. However, photovoltaic solar panels systems incorporate a power electronics front end, which influence on the quality of supply in regards to voltage harmonics. Harmonics affect quality of supply, reliable operation of system equipment as well as component life expectancy.